A BIBLIC PARABLES IN THE EPISTLES OF SAINT CLEMENT,PATRIARCH OF ROME, WRITTEN BY EPISCOPE ST. CLEMENT OF OHRID - Milovska, Dobrila (International Scientific Journal Vision, 2019)
The epistles of praise of St. Clement of Ohrid were written in accordance with the form of the Byzantine epistles of praise. Their dominant characteristics include emotionality, dynamism and musicality. They were written in accordance with the form used bythe hymns and megalynarions which were read during the ceremonious religious services. The epistles of praise of St. Clement of Ohrid have the characteristics of a hymn. Their main characteristic is the prominence of religious stories. The epistles praisethe heroes of the Church of Christ (such as the case in the Epistle of St. Clement, patriarch of Rome) and the other saints. The epistles of St. Clement of Ohrid give prominence to the stylistic and lingual adeptness of the author, which is full of emotion and beauty. St. Clement makes use of various epithets, comparisons, antitheses, dramatic situations, hymnologic forms. He most often uses comparisons to: the sun, the light, the dawn, the rays of light, the shining etc., which infuse the epistle with vivacity, light, optimism and hope. In the first part, after the short poetic introduction, St. Clement makes use of therepetition of the same words to construct a rhythmic-intonational whole, as the most effective way of praising the saint.In the final part, the saint floods the hero with praise with selected words from the Christian religion.